Effects of the Common Agricultural Policy potential scenarios after 2013 in the Slovak Republic - Eva UHRINČAŤOVÁ (Agricultural Economics (AGRICECON), 2011)
The contribution presents the modelling solution of the potential scenarios impact of the Common Agricultural Policy of the European Union after 2013 in the selected sectors of the Slovak Republic national economy. The solution is accomplished using the Computable General Equilibrium model with the emphasis on the productive and less favourable agricultural areas and the theoretical rents for agricultural land. If we take into consideration both pillars of the Common Agricultural Policy of the European Union, according to the modelling calculations in Slovak conditions the most favoured is the Conservative scenario, the Reference and the Flat Rate scenario are neutral and the least favourable is the Liberalisation scenario.